Market Reaction to the Class Action Fairness Act of 2005 - WOLFSON, Shael; MUKHERJEE, Tarun (Journal of Advanced Research in Law and Economics, 2017)
The Class Action Fairness Act of 2005 (CAFA) virtually removed the majority of class-action jurisdiction from State to Federal Courts. We examine the market reaction to various events leading to the passage of CAFA and find that stockholders of companies likely to be affected by CAFA react positively (negatively) to the events that increase (decrease) the chances of passage. We examine the strength of this finding by testing three complementary hypotheses: one, companies susceptible to product-liability litigation display greater sensitivity to CAFA than companies exposed to contract litigation; two, the market reaction would be more positive for companies with better corporate governance and transparency to events favoring the passage of CAFA; three, because a positive market reaction implies that stockholders favor Federal Courts over State Courts as a venue, they would react negatively when a class-action is remanded from a  State to a Federal Court.  Our results support these hypotheses, indicating that stockholders prefer Federal Courts to State Courts for class-action jurisdiction.